Quantitative Assessment of Soil and Water Loss in the Nanpan and Beipan River Basins Based on CSLE Model - LIU Xiaolin; SHI Yandong; ZENG Xiaolei; HUANG Hairong; YIN Bin (Renmin Zhujiang)
The quantitative assessment of soil and water loss can provide a scientific basis for preventing and controlling soil and water loss disasters and implementing ecological environmental construction.Based on the spatial analysis and data management functionalities on the ArcGIS platform with multisource remote sensing imagery used as the information source,the data of land use,vegetation cover,and terrain slope in the Nanpan River and Beipan River basins were obtained.The soil erosion modulus was calculated by employing China soil loss equation (CSLE),yielding monitoring results for soil and water loss in the Nanpan River and Beipan River basins.The results show that in 2021, the total area affected by soil and water loss in the Nanpan River and Beipan River basins was 23 966.97 km2,primarily characterized by mild erosion intensity.Soil and water loss in the northeast part of the basins was more severe than that in the southwest part.The phenomenon mainly occurred in arable land,woodland,and grassland,accounting for over 90% of the total soil and water loss area,with vegetation cover at all levels showing a prevalence of mild and moderate erosion.Soil and water loss in the entire region mainly occurred in slope grades ranging from 6° to 35°.In general,the issue of soil and water loss remains prominent in specific regions of the Nanpan and Beipan River basins.It is necessary to adopt a combined approach of prevention and remediation to address this issue and improve the overall situation.